Strengthening Self-Regulated Learning in Islamic Religious Education: Practical Strategies Based on Educational Psychology to Enhance Students’ Learning Autonomy - Royhan Ikhwan; Eva Latipah (Linguanusa : Social Humanities, Education and Linguistic, 2026)
Introduction to The Problem: The shift from teacher-centered learning to student-centered learning in the 21st century requires learners to develop greater autonomy in managing their learning processes. Self Regulated Learning (SRL) is recognized as a key competency that enables students to plan, monitor, and evaluate their learning independently. In the context of Islamic Religious Education (PAI), SRL is not only associated with academic achievement but is also supported by Islamic values such as responsibility, selfawareness (muhasabah), and lifelong learning. Purpose: This study aims to examine the theoretical foundations of Self-Regulated Learning from educational psychology and Islamic psychology perspectives, identify factors influencing SRL in PAI learning, and formulate practical strategies for strengthening students’ learning autonomy. Design/methods/approach: This study employed a qualitative descriptive approach using library research. Data were collected from books, scientific journals, and relevant scholarly publications concerning SRL, educational psychology, developmental psychology, and Islamic education. The collected data were analyzed using content analysis to identify major concepts, influencing factors, and practical implications for PAI learning. Findings: The literature review indicates that self-efficacy, learningmotivation, metacognitive  ability, teacher support, and learning environment are important determinants of SRL. The analysis also identified several practical strategies for strengthening SRL in PAI, including Islamic value-based goal setting, self-monitoring through muhasabah learning journals, project-based learning, utilization of diverse learning resources, spiritual-academic reflection, and the integration of digital technology. These strategies are theoretically supported by contemporary educational psychology and aligned with Islamic educational values. The findings are limited to conceptual and theoretical analysesderived from secondary sources; therefore, they cannot be generalized to all educational settings without empirical verification. Future studies should examine the effectiveness of the proposed strategies throughclassroom-based and quantitative research designs. This article contributes by integrating contemporary Self-Regulated Learning theory with Islamic educational values and psychological perspectives, offering a conceptual framework that can assist PAI teachers in fostering students’ learning autonomy while maintaining the spiritual and moral objectives of Islamic education.